Wildlife Preservation and Public Enlightenment: An In-Depth Analysis of Kanpur Zoological Park’s Contribution to Conservation and Education - Nithilan K. M.; Sundaram, Asha; Anil, Girija (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Sprawling over 76.56 hectares, the Kanpur Zoological Park (KZP) is the largest open green space in Kanpur and the largest zoological park in North India. Housing over 1,400 animals representing nearly 125 species, KZP serves as a crucial sanctuary for endangered wildlife. Notably, they participate in breeding programs for critically endangered species like the white tiger (with a captive population of 3 at KZP) and the Himalayan black bear (currently housing 5 individuals). KZP's rehabilitation efforts have successfully released 23 Indian pangolins back into their natural habitat since 2010, contributing directly to the conservation of this threatened species.In the realm of education, KZP offers a diverse range of programs, reaching over 800,000 students annually. These programs include interactive exhibits, guided tours, and educational workshops, fostering environmental awareness and appreciation for biodiversity. However, challenges remain, including ensuring the ethical welfare of animals in captivity and measuring the long-term impact of educational programs on visitor behavior.By embracing new technologies, fostering collaboration with other organisations, and prioritising ethical practices, KZP has the potential to significantly improve its impact. This can include initiatives like utilising VR technology to enhance visitor engagement with animal habitats (studies suggest VR experiences can increase knowledge retention by up to 20%) and developing standardised assessment methods to measure the effectiveness of educational programs. By addressing these challenges and leveraging its strengths as a prominent green space and conservation centre, KZP can become a leading force in inspiring future generations to become stewards of the environment.